Adult Trees Cryptomeria japonica (Thunb. ex L.f.) D. Don Micropropagation: Factors Involved in the Success of the Process - Rojas Vargas, Alejandra (2023)
Financiado por el Departamento de Junta de Becas de la Universidad Nacional de Costa Rica y por el proyectos: MINECO (AGL2016-76143-C4-3R), MICINN (PID2020-112627RB-C32), CYTED (P117RT0522), MULTIFOREVER project, under the umbrella of ERA-NET Cofund ForestValue by ANR (FR), FNR (DE), MINCyT (AR), MINECO-AEI (ES), MMM (FI), VINNOVA (SE). ForestValue has received funding from the European Union’s Horizon 2020 Research and Innovation Programme under grant agreement no. 773324 y al DECO (Basque government).